Implementation Of The Kampung Madani Program Based On Community Participation In Pokmas Dapur Ceria Village, Dr. Soetomo Village - Pancawardani, Nur Ratna Wulan Kartini; Mustofa, Amirul (PT. Anagata Sembagi Education, 2025)
The purpose of the research is to identify how the Kampung Madani Program can be implemented effectively through a participatory approach to Pokmas Dapur Ceria of Dr. Soetomo Village. This study also seeks to explore the best strategies to encourage active community collaboration, with a focus on increasing the capacity of Pokmas Dapur Ceria as a community of change at the local level. This study uses qualitative research. The location of the research is in Dr Soetomo Village. The data collection methods used include literature studies, and document data. Based on the results of research on the Madani Village Program which was carried out through Pokmas Dapur Ceria in Dr. Soetomo Village, it succeeded in improving social, economic, and public health welfare. The main challenges of the program are limited food distribution coverage and uneven community involvement. The practical implications of the participatory approach of the Kampung Madani Program are effective in increasing the sense of belonging and social solidarity, becoming a model of local empowerment that can be applied in other regions.